تمويل المشاريع الاقتصادية بين الصناعة المالية الاسلامية و التقليدية - عجيلة, محمد; حجاج, يوسف (جامعة الوادي - University of Eloued, 2021)
بتاريخ الثلاثاء 3 أوت 2020 اطلق البنك الوطني الجزائري رسميا نشاط الصيرفة الإسلامية من خلال تسويق منتجات مطابقة لتعاليم الشريعة الإسلامية. ويندرج هذا النشاط الجديد ضمن توجيهات السلطات العليا في البلاد من أجل ارساء حركية اكثر فعالية وتنوع للسوق المالية الوطنية ودفع عجلة التنمية الاقتصادية قدما. وقد طرح البنك الوطني الجزائري مجموعة ثرية من صيغ التمويل والادخار منتجات مصممة لتلبية الطلب الملح والمرصود لمختلف فئات المجتمع . تهدف هذه الورقة البحثية إلى التعريف بالصناعة المالية الإسلامية باعتبارها تطرح أدوات مستحدثة والفرق بينها وبين التقليدية إضافة إلى الصيغ التمويلية التي تستخدم لتمويل مشاريع الاستثمار ومشاريع الاستغلال. On Tuesday 3 October 2020, the National Bank of Algeria officially launched Islamic banking by marketing products that conform to Islamic law. This new activity is part of the guidance of the highest authorities of the country in order to establish a more effective and diversified national financial market and to advance economic development. The National Bank of Algeria has launched a rich set of financing and savings products designed to meet the urgent demand for various social groups. The aim of this paper determinate the concept of the Islamic financial industry will be taken up as offering up-to-date tools and the difference between them and the traditional ones, as well as the financing formulas used to finance investment and exploitation projects.
Keywords: تمويل ; صيرفة ; صناعة مالية ; كفاءة ; فعالية